Effective Lighting In 2d Animation Based On Steven Universe - Nurul Saidatul Nazwa, Binti Bolhan (Universiti Malaysia Sarawak (UNIMAS), 2018)
Lighting is the most basic special effect that should be considered when enhancing the look of the animation. By adding a proper lighting, it can create depth and volume into the character and also creating more believable environment in animation (n/a, 2017). The purpose of this study is to study how the lighting enhance and affecting the mood in fantasy 2D animation. The importance of this study is to how to create the effective lighting in flat 2D animation. This study will be conducted by using quantitative method. The researcher will be compare the type of light and effects of mood in animation. Researcher also will be observed some cartoon series in tenns of light and the mood. This study will be used as a reference for future research.